Miniplates orientation for fracture fixation of the mandibular condyle - Abdul Kadir, Mohammed Rafiq; Haron, H.; Kamsah, N.; Nordin, N. (Springer Berlin Heidelberg, 2008)

(untitled)
Mandibular fractures at the condylar region are normally treated with miniplates made of high stiffness and strength metallic materials. Rigid fixation is important to maintain the position of the two bone segments, thus improving the chances of bone union. Failure to achieve adequate stability will result in malunion or nonunion. In this study, two different orientations of miniplates were used to analyse the primary stability of the fractured site using finite element method. Three dimensional model of a mandible was reconstructed from CT dataset, and a low subcondylar fracture was simulated on the right side of the mandible. A straight 4-hole miniplate was modeled and placed onto the condylar neck axis and fixed with 2 screws, 2mm in diameter and 7mm long on either side of the fracture line. Two different orientations of the miniplates were used for comparison of primary stability and load transfer to the bone — along the condylar neck and below the mandibular notch. Non-linear contact analysis was used and the bone segments were allowed to slide against each other. Results showed that interface micromotion and stress distribution was larger for the miniplate positioned along the condylar neck compared to the one placed below the mandibular notch. For maximum stability, it is advisable to fix the straight miniplate across the fractured segment below the condylar notch.